Springtime daily variations in lower-tropospheric ozone over east Asia: the role of cyclonic activity and pollution as observed from space with IASI - G. Dufour; M. Eremenko; J. Cuesta; C. Doche; G. Foret; M. Beekmann; A. Cheiney; Y. Wang; Z. Cai; Y. Liu; M. Takigawa; Y. Kanaya; et al. (Atmospheric Chemistry and Physics, 2015)
We use satellite observations from IASI (Infrared Atmospheric Sounding Interferometer) on board the MetOp-A satellite to evaluate the springtime daily variations in lower-tropospheric ozone over east Asia. The availability of semi-independent columns of ozone from the surface up to 12 km simultaneously with CO columns provides a powerful observational data set to diagnose the processes controlling tropospheric ozone enhancement on synoptic scales. By combining IASI observations with meteorological reanalyses from ERA-Interim, we develop an analysis method based only on IASI ozone and CO observations to identify the respective roles of the stratospheric source and the photochemical source in ozone distribution and variations over east Asia. The succession of low- and high-pressure systems drives the day-to-day variations in lower-tropospheric ozone. A case study analysis of one frontal system and one cut-off low system in May 2008 shows that reversible subsiding and ascending ozone transfers in the upper-troposphere–lower-stratosphere (UTLS) region, due to the tropopause perturbations occurring in the vicinity of low-pressure systems, impact free and lower-tropospheric ozone over large regions, especially north of 40° N, and largely explain the ozone enhancement observed with IASI for these latitudes. Irreversible stratosphere–troposphere exchanges of ozone-rich air masses occur more locally in the southern and southeastern flanks of the trough. The contribution to the lower-tropospheric ozone column is difficult to dissociate from the tropopause perturbations generated by weather systems. For regions south of 40° N, a significant correlation has been found between lower-tropospheric ozone and carbon monoxide (CO) observations from IASI, especially over the North China Plain (NCP). Considering carbon monoxide observations as a pollutant tracer, the O3–CO correlation indicates that the photochemical production of ozone from primary pollutants emitted over such large polluted regions significantly contributes to the ozone enhancements observed in the lower troposphere via IASI. When low-pressure systems circulate over the NCP, stratospheric and pollution sources play a concomitant role in the ozone enhancement. IASI's 3-D observational capability allows the areas in which each source dominates to be determined. Moreover, the studied cut-off low system has enough potential convective capacity to uplift pollutants (ozone and CO) and to transport them to Japan. The increase in the enhancement ratio of ozone to CO from 0.16 on 12 May over the North China Plain to 0.28 over the Sea of Japan on 14 May indicates photochemical processing during the plume transport.